Avian influenza A viruses: from zoonosis to pandemic. (May 2014) - Richard, Mathilde; Graaf, Miranda de; Herfst, Sander
Zoonotic influenza A viruses originating from the animal reservoir pose a threat for humans, as they have the ability to trigger pandemics upon adaptation to and invasion of an immunologically naive population. Of particular concern are the H5N1 viruses that continue to circulate in poultry in numerous countries in Europe, Asia and Africa, and the recently emerged H7N9 viruses in China, due to their relatively high number of human fatalities and pandemic potential. To start a pandemic, zoonotic influenza A viruses should not only acquire the ability to attach to, enter and replicate in the critical target cells in the respiratory tract of the new host, but also efficiently spread between humans by aerosol or respiratory droplet transmission. Here, we discuss the latest advances on the genetic and phenotypic determinants required for avian influenza A viruses to adapt to and transmit between mammals.